Investigation of Nurses Views on Nursing Assistant Duties - Fadime Ulupınar; Manar Aslan (Association of Nurse Managers, 2019)
INTRODUCTION: In Turkey, nursing assistants who will give their first graduates to the field in 2018 will continuously work in cooperation with the nurses. Therefore, the fact that the members of these two professional groups do not have enough knowledge about each other's duties can cause conflicts in health institutions as well as bring legal problems. For this reason, it is important what nurses think about the nurse assistant duties. This study was carried out to evaluate the opinions of the nurses about duties of the nursing assistants. METHODS: This is a descriptive research and consisted of 438 nurses working in two medical faculties,two private hospitals, located in a city center, who volunteered to participate in the research. During the collection of data, a questionnaire form was used which included the participants descriptive characteristics, their opinions on practice of nursing assistant, and the implementations involving duty-task distributions. RESULTS: According to the findings, 20.8% of the nurses stated there is no information about the nursing assistant practice and 32.2% about duty-task definitions. 36.8% of the nurses think the need for nursing assistant practice, 30.6% of them think this practice will reduce nursing employment. 39% of the nurses think the nursing assistant practice will reduce the workload of nurses and 55.7% of them think there will be duty-task complexity. It was also seen nurses have opinions that are not in line with the valid regulations related to the nurse and nurse assistant. Besides, it was found there was a significant difference between the nurses' opinions nursing assistans duties and some of the socio-demographic and work characteristics. DISCUSSION AND CONCLUSION: It has been determined there are different opinions about practice among nurses. It can be said the opinions of the nurses, which are not in line with the regulations in force, give some hints that work-task chaos may occur.